2009
DOI: 10.4149/neo_2009_05_387
|View full text |Cite
|
Sign up to set email alerts
|

Brazilein inhibits survivin protein and mRNA expression and induces apoptosis in hepatocellular carcinoma HepG2 cells

Abstract: Hepatocellular carcinomas represent the third leading cause of cancer-related deaths worldwide. Survivin, a structurally unique member of the inhibitor of apoptosis protein (IAP) family, is overexpressed in a wide range of malignancies, including hepatocellular carcinoma. Due to its involvement in cancer progression and treatment resistance, survivin is currently undergoing extensive investigation as a novel intervention target to induce apoptosis in cancer cells by phytochemicals or synthetic agents. Brazilei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
(19 reference statements)
2
14
0
1
Order By: Relevance
“…It has already been reported that the cytotoxic effect of brazilein on Hep G2 cells occured via apoptosis induction and survivin protein expression suppression (Zhong, et al, 2009). …”
Section: Brazilein Increased Doxorubicin's Cytotoxicity On Mcf-7/dox mentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been reported that the cytotoxic effect of brazilein on Hep G2 cells occured via apoptosis induction and survivin protein expression suppression (Zhong, et al, 2009). …”
Section: Brazilein Increased Doxorubicin's Cytotoxicity On Mcf-7/dox mentioning
confidence: 99%
“…1) have cytotoxic effect on lung cancer cells, nasopharyngeal cancer cells, and prostate cancer cells with IC 50 value of 5-18 µM (Yen, et al, 2010). Brazilein inhibits survivin protein and induces apoptosis in HepG2 hepatocellular carcinoma cells (Zhong, et al, 2009). This study was conducted to evaluate the cytotoxic effect of brazilein, both alone and in combination with doxorubicin on MCF-7/DOX cells by using MTT assay.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the inhibitors of apoptosis proteins, such as XIAP and survivin, are abnormally expressed in hepatocarcinoma cells and they have been confirmed as therapeutic targets for natural products (30)(31)(32). We further evaluated the effects of the combination treatment of curcumin and resveratrol on XIAP and survivin expression in Hepa1-6 cells.…”
Section: Combined Effects Of Resveratrol and Curcumin On Expression Omentioning
confidence: 99%
“…In addition, brazilin also increased the population of glioblastoma cells in cell cycle sub-G1 area (Lee, et al, 2013). While the other major compound of secang's heartwood, like brazilein, also known could increase the activation of caspase-9 and caspase-3, induce PARP cleavage and cause down-regulation of survivin protein on HepG2 liver cancer cells (Zhong, et al, 2009). On MCF-7 breast cancer cells, brazilein also could induce apoptosis through inhibition of survivin expression (Tao, et al, 2011).…”
Section: (D) (E)mentioning
confidence: 99%